Hölder continuity and the Harnack inequality for the solutions of an elliptic equation containing the $p$ -Laplacian and uniformly degenerating in a part of the domain - Huseynov, S. T. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider quasilinear equations of the $p$-Laplacian type uniformly degenerating in a part of the domain. An analog of theHarnack inequality is proved for nonnegative solutions and the Holder continuity of the solutions is established by usingthis inequality.